Comparative Study of Layout Design of Non- Profit Senior Care Centres in Cheras - Low, Joo Yin; Aminuddin, Asrul (MAJ - Malaysia Architectural Journal, 2019)
The increase population of elderly has become a topic to be concerned in many developing countries. In Malaysia, the population is ageing and our country is forecasted to become an aged nation by 2030 due the rapid demographic shift. Seniors from wealthier background have much more options to choose from private and profit orientated care centres, which generally have better facilities and environment than the others. From the perspective of elderly who cannot afford this option, design of the accommodation that caters for this ageing community usually neglected their comfort and needs. This paper focuses on the three non-profit care centres in Cheras, evaluating their appropriateness of the layout design in creating a senior friendly environment as well as identifying their limitation and opportunities to support healthy ageing. Observation and photography record was carried out in the care centres to analyse its layout design through its accessibility, safety and comfortably. It is found out that the design scheme have much more to improve in order to support the health and well-being for elderly. This paper outlines the challenges of current non-profit care centres for elderly in Cheras and highlights aspects crucial for consideration in creating a senior friendly environment for their healthy ageing.